Law against the state: ethnographic forays into law's transformations - Eckert, Julia Maria; Donahoe, Brian; Strümpell, Christian; Biner, Zerrin Özlem; Eckert, Julia (Cambridge studies in law and society, 2012)
"This collection of rich, empirically grounded case studies investigates the conditions and consequences of 'juridification' - the use of law by ordinary individuals as a form of protest against 'the state'. Starting from the actual practices of claimants, these case studies address the translation and interpretation of legal norms into local concepts, actions and practices in a way that highlights the social and cultural dynamism and multivocality of communities in their interaction with the law and legal norms. The contributors to this volume challenge the image of homogeneous and primordially norm-bound cultures that has been (unintentionally) perpetuated by some of the more prevalent treatments of law and culture. This volume highlights the heterogeneous geography of law and the ways boundaries between different legal bodies are transcended in struggles for rights. Contributions include case studies from South Africa, Malawi, Sierra Leone, Turkey, India, Papua New Guinea, Suriname, the Marshall Islands and Russia"--